Counting - Bryant-Mole, Karen; Mukhida, Zul (Milwaukee : Gareth Stevens Pub., 2000)
A teddy bear introduces the numbers from one to ten with words, numerals, and pictures.
Includes index.
Keywords: Counting -- Juvenile literature; Counting books